IMPACT OF SOCCER-SPECIFIC SKILL TRAINING ON PHYSICAL AND PSYCHOLOGICAL ATTRIBUTES IN COMPETITIVE PLAYERS - Krishnakumar S.; R. Ramakrishnan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examined whether soccer-specific skill training affects competitive college-level soccer players’ physical and psychological qualities. Soccer needs physical fitness, technical talent, and mental toughness. The experimental group (n = 20) and the control group (n = 20) of 40 male collegiate soccer players aged 18–23 were randomly allocated. For six weeks, the experimental group practiced soccer-specific technical activities to improve agility, coordination, speed, and endurance. Additionally, the training included competitive and incentive elements to boost self-confidence, focus, and anxiety control. The control group-maintained training without intervention. Standardized physical fitness and psychological tests were used pre- and post-intervention. Statistical analysis showed significant improvements (p < 0.05) in physical and psychological factors for the experimental group compared to the control group. The study finds that competitive college soccer players can increase their physical performance and psychological preparation by adding soccer-specific skill training to their practice routines. Coaches and sports scientists should use tailored training to develop athletes holistically.